Construction time prediction: The forgotten service - Pearl, Rob; Bowen, Paul (Acta Structilia, 2002)
The effective management of construction project cost. quality and time is essential for the attainment of client objectives. While consultant’s roles in respect of cost (price) and quality issues are well recognised, less attention is paid to the equally important aspect of construction time assessment. This article describes an experiment conducted with South African contractors and consultants to determine the way in which they forecast project construction time. within the constraints of a preferred procurement model.